El enfoque de John Dewey y la escuela activa en educación inicial - Changoluisa Chicaiza, Karen Stefania (2022)
The present investigation showed that John Dewey's approach is related to the Active School in Initial Education, the same one that arises in the first experiences that he maintains during his preschool stage when relating in a social environment and therefore it was shown that the teachers they present a lack of knowledge about John Dewey's theory. Faced with this, it has been proposed as an objective, to diagnose the pedagogical approach of John Dewey through the application of the active school to strengthen the teaching-learning process in the children of the Semillitas Initial Education Center "César Francisco Naranjo Rumazo". This research had a mixed qualitative-quantitative approach, with an exploratory, descriptive research type and with a feasible and applied project modality; the techniques used were an interview with the director of the institution, a survey of the teachers and an observation sheet applied to the children. According to the applied survey, it was determined that 50% of the teachers surveyed state that they always maintain flexible communication with their children, achieving flexible communication between teachers and children in the classroom; Thus, it was also found that 50% of the teachers surveyed state that they always pay attention to the children since they carry a great responsibility from home, since children in early childhood need a lot of attention and this entails a great deal of responsibility. responsibility to parents and teachers. Concluding with the investigation, the pedagogical conception of the Pedagogue in early childhood presents a relationship with the integral development of the child, being one of the optimal tools for learning, since it is always focused on the use of innovative activities that help the child. in their personal or academic development at the Semillitas Initial Education Center "César Francisco Naranjo Rumazo".